S-Ketamine Oral Thin Film—Part 1: Population Pharmacokinetics of S-Ketamine, S-Norketamine and S-Hydroxynorketamine - Simons, Pieter; Olofsen, Erik; van Velzen, Monique; van Lemmen, Maarten; Mooren, René; van Dasselaar, Tom; Mohr, Patrick; Hammes, Florian; van der Schrier, Rutger; Niesters, Marieke; Dahan, Albert (Frontiers in Pain Research, 2022)
Ketamine is administered predominantly via the intravenous route for the various indications, including anesthesia, pain relief and treatment of depression. Here we report on the pharmacokinetics of sublingual and buccal fast-dissolving oral-thin-films that contain 50 mg of S-ketamine in a population of healthy male and female volunteers. Twenty volunteers received one or two oral thin films on separate occasions in a randomized crossover design. The oral thin films were placed sublingually (n = 15) or buccally (n = 5) and left to dissolve for 10 min in the mouth during which the subjects were not allowed to swallow. For 6 subsequent hours, pharmacokinetic blood samples were obtained after which 20 mg S-ketamine was infused intravenously and blood sampling continued for another 2-hours. A population pharmacokinetic analysis was performed in NONMEM to construct a pharmacokinetic model of S-ketamine and its metabolites S-norketamine and S-hydroxynorketamine. P-values < 0.01 were considered significant. S-ketamine bioavailability was 26 ± 1% (estimate ± standard error of the estimate) with a 20% lower bioavailability of the 100 mg oral thin film relative to the 50 mg film, although this difference did not reach the level of significance. Due to the large first pass-effect, 80% of S-ketamine was metabolized into S-norketamine leading to high plasma levels of S-norketamine following the oral thin film application with 56% of S-ketamine finally metabolized into S-hydroxynorketamine. No differences in pharmacokinetics were observed for the sublingual and buccal administration routes.The S-ketamine oral thin film is a safe and practical alternative to intravenous S-ketamine administration that results in relatively high plasma levels of S-ketamine and its two metabolites.